2016
DOI: 10.1002/elan.201600591
|View full text |Cite
|
Sign up to set email alerts
|

AgNP/Bi/Nafion‐modified Disposable Electrodes for Sensitive Zn(II), Cd(II), and Pb(II) Detection in Aerosol Samples

Abstract: 1IntroductionHumane xposure to aerosolized particulate matter( PM) has been recognized worldwide as am ajor contributor to morbidity and mortality [1][2][3]. PM is chemically complex, containing aw ide range of inorganic and organic molecules that can cause adverse healthe ffects. Understanding exposure can be difficult due to the spatial heterogeneity of PM and the large variety of PM sources [4,5].F urther exacerbating problems associatedw ith PM exposure,p articularly for human health, is that the quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The solvent is evaporated before reaching the surface, where the NPs are deposited [ 67 ]. Mettakoonpitak et al [ 68 ] reported using electrospray for the deposition of silver nanoparticles on SPEs.…”
Section: Spes Modification By Physical Approachesmentioning
confidence: 99%
“…The solvent is evaporated before reaching the surface, where the NPs are deposited [ 67 ]. Mettakoonpitak et al [ 68 ] reported using electrospray for the deposition of silver nanoparticles on SPEs.…”
Section: Spes Modification By Physical Approachesmentioning
confidence: 99%
“…Compared with the bare GCE, the peak current of Bi/GCE is enhanced by a factor of 2.72. This remarkably increasing sensitivity can be attributed to the ability of bismuth to form the fused alloy with Cd, which makes Cd(II) easier reduction, improving the stripping peak current . Moreover, the N‐HPCSs/GCE displays a 337 % peak height enhancement for Cd(II) over the bare GCE.…”
Section: Resultsmentioning
confidence: 99%
“…CSPEs were prepared as previously described [3638]. Home-made electrode inks were created by adding 0.43 g graphite to 1.00 g of the commercial carbon ink followed by hand mixing until homogeneous.…”
Section: Methodsmentioning
confidence: 99%